BRONZE FIGURINE OF THE VILLAGE IRGALI - Omarov, I I; Seferbekov, M R (History, Archeology and Ethnography of the Caucasus, 2016)
The authors of the article describe the medieval bronze figurine of a woman with outstretched hands, perhaps holding a vessel and/or in a posture of adoration, which was found on the mountain Mazhi near the village Irgali in Levashinsky district of Dagestan. In the researchers’ opinion, the bronze figurines found in the Caucasus are probably earth-gods and regulators of the weather, patrons of the society or mediators between gods and people. The figurine under consideration has numerous analogues in ancient and medieval bronze anthropomorphic plastic art of the Caucasus. The image also parallels the ritual practice of the Tindi people from the village Echeda, in which a woman with a wooden measure for corn in her hands took part. The authors consider that the figurine is one of incarnations ofthe image of the Great Mother Goddess in the positive aspects of her functions and is related to fertility, patronage of the particular society, family, woman and childbearing, orolatry, the world mountain (invariant of the world tree), space top in the tripartite picture of the world.
Keywords: bronze anthropomorphic plastic art; mountain; fertility cult; Great Mother Goddess